Mono-6-Deoxy-6-Aminopropylamino-β-Cyclodextrin on Ag-Embedded SiO(2) Nanoparticle as a Selectively Capturing Ligand to Flavonoids - Hahm, Eunil (Nanomaterials (Basel), 2019)
It has been increasingly important to develop a highly sensitive and selective technique that is easy to handle in detecting levels of beneficial or hazardous analytes in trace quantity. In this study, mono-6-deoxy-6-aminopropylamino-β-cyclodextrin (pr-β-CD)-functionalized silver-assembled silica nanoparticles (SiO(2)@Ag@pr-β-CD) for flavonoid detection were successfully prepared. The presence of pr-β-CD on the surface of SiO(2)@Ag enhanced the selectivity in capturing quercetin and myricetin among other similar materials (naringenin and apigenin). In addition, SiO(2)@Ag@pr-β-CD was able to detect quercetin corresponding to a limit of detection (LOD) as low as 0.55 ppm. The relationship between the Raman intensity of SiO(2)@Ag@pr-β-CD and the logarithm of the Que concentration obeyed linearity in the range 3.4–33.8 ppm (R(2) = 0.997). The results indicate that SiO(2)@Ag@pr-β-CD is a promising material for immediately analyzing samples that demand high sensitivity and selectivity of detection.